Production of Sm-153 With Very High Specific Activity for Targeted Radionuclide Therapy - Van de Voorde, Michiel; Duchemin, Charlotte; Heinke, Reinhard; Lambert, Laura; Chevallay, Eric; Schneider, Thomas; Van Stenis, Miranda; Cocolios, Thomas Elias; Cardinaels, Thomas; Ponsard, Bernard; Ooms, Maarten; Stora, Thierry; et al. (Frontiers in Medicine, 2021)
Sm-153 is a highly interesting radionuclide within the field of radionuclide therapy because of its favorable decay characteristics. Sm-153 has a half-life of 1.93 d and decays into a stable daughter nuclide (Eu-153) whereupon β- particles (E = 705 keV (30%), 635 keV (50%)) are emitted suitable for therapy. Sm-153 also emits γ photons (103 keV (28%)) allowing for SPECT imaging, which is of value in theranostics. The full potential of Sm-153 in nuclear medicine is currently not being exploited because of the radionuclide's limited specific activity available due to its carrier added production route. In this work, a new production method was developed to produce Sm-153 with higher specific activity, allowing for its potential use in targeted radionuclide therapy. Sm-153 was efficiently produced via neutron irradiation of a highly enriched Sm-152 target (98.7% enriched, σth = 206 b) in the BR2 reactor at SCK CEN. Irradiated target materials were shipped to CERN-MEDICIS, where Sm-153 was isolated from the Sm-152 target via mass separation (MS) in combination with laser resonance enhanced ionization to drastically increase the specific activity. The specific activity obtained was 1.87 TBq/mg (≈ 265 times higher after the end of irradiation in BR2 + cooling). An overall mass separation efficiency of 4.5% was reached on average. Further radiochemical purification steps were developed at SCK CEN to recover the Sm-153 from the MS target to yield a solution ready for radiolabeling. Each step of the radiochemical process was fully analyzed and characterized for further optimization resulting in a high efficiency (overall recovery: 84%). The obtained high specific activity (HSA) Sm-153 was then used in radiolabeling experiments with different concentrations of 4-isothiocyanatobenzyl-1,4,7,10-tetraazacyclododecane tetraacetic acid (p-SCN-Bn-DOTA). Even at low concentrations of p-SCN-Bn-DOTA, radiolabeling of 0.5 MBq of HSA Sm-153 was found to be efficient. In this proof-of-concept study, we demonstrated the potential to combine neutron irradiation with mass separation to supply high specific activity Sm-153. Using this process, 153SmCl3 suitable for radiolabeling, was produced with very high specific activity allowing application of Sm-153 in targeted radionuclide therapy. Further studies to incorporate Sm-153 in radiopharmaceuticals for targeted radionuclide therapy are ongoing.